1994
DOI: 10.1007/bf00193686
|View full text |Cite
|
Sign up to set email alerts
|

Leaf, stolon and root growth of white clover (Trifolium repens L.) in response to irrigation with saline water

Abstract: The effect of irrigation with water at salinity concentrations of 2.6 and 5.2 dS m -1 on the growth of pure swards of six cultivars of white clover (Trifolium repens L.) was examined over three irrigation seasons at Tatura, Victoria, Australia. After two irrigation seasons, soil EC e levels increased to 6 dS m -t at 0-60 cm depth in the higher salinity treatment resulting in highly significant (p<0.001) reductions in shoot dry matter production, flowering densities and petiole and stolon densities. These salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Rogers et al (1994) reported that concentrations of Na and Cl in the shoots of white clover linearly increased with increasing soil EC e levels above 1 dS/m, and values were negatively related to shoot dry matter production. In the present study, K/Na ratio in stems had a slightly greater positive correlation with stem dry mass than the corresponding correlation in roots (Fig.…”
Section: Correlation Between Dry Matter Production and Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rogers et al (1994) reported that concentrations of Na and Cl in the shoots of white clover linearly increased with increasing soil EC e levels above 1 dS/m, and values were negatively related to shoot dry matter production. In the present study, K/Na ratio in stems had a slightly greater positive correlation with stem dry mass than the corresponding correlation in roots (Fig.…”
Section: Correlation Between Dry Matter Production and Ionsmentioning
confidence: 99%
“…Similar results were also found in other studies (Cai et al, 2014;Muhammad Jafar et al, 1991;Niu et al, 2013). The influence of salinity on flowers was higher than that on vegetative growth, indicating that reduced reproductive growth may have important implications for the persistence of vegetative growth under continued saline irrigation (Rogers et al, 1994). Therefore, control of vegetative growth by pruning may be an effective measure to ensure relatively high production of rose flowers under saline irrigation.…”
Section: Rose Growth and Plant Water Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing the WP, production and water use of three perennial forage legumes (white clover, red clover and lucerne), at three different irrigation intervals, Kelly et al [33] showed white clover to be more sensitive to variations in irrigation frequency than either red clover or lucerne. This was attributed to its relatively shallow root structure and density with most of its roots located in the top 20 cm of the soil profile [44][45][46] and therefore its inability to access soil water stored at depth. White clover was also shown to be the least tolerant to deficit irrigation of 15 forage species evaluated in a humid subtropical climate at Camden, NSW, which again was attributed to its root architecture and density [12,47].…”
Section: Perennial Foragesmentioning
confidence: 99%
“…Increasing soil salinization yearly at a rate of 10% accelerates the demand for salt-tolerant crop germplasms to maintain agricultural yield worldwide ( Shrivastava and Kumar, 2015 ). For the evaluation of salt tolerance in white clover species, the study by Rogers et al (1994) found that cv. Haifa and cv.…”
Section: Discussionmentioning
confidence: 99%